Surgical outcome of phacofragmentation and phacoemulsification in senile white mature cataract (Medical Journal of Indonesia, 2003)
Purpose : To compare the effectiveness and safety of phacofragmentation and phacoemulsification techniques on senile white mature cataract. Methods : Prospective, double masked, randomized study comprises 32 eyes of senile white mature cataract randomly divided into 2 groups, 16 eyes had phacofragmentation (group I) and 16 eyes had phacoemulsification (group II). The evaluated safety parameters were pupil diameter pre surgery and prior to intra ocular lens (IOL) implantation, corneal thickness and flaremeter. Nucleus delivery, uncorrected visual acuity (UCVA) and surgically induced astigmatism (SIA) were the effectiveness parameters. Follow-up were scheduled for post-operative day 1,7,15 and 30. Results : prior to the surgery there were no significant differences in age, visual acuity, corneal thickness and flaremeter between two groups. Pre surgical and prior to IOL implantation mean pupilarry diameters in both groups were not significantly different. There was no significant difference in pupillary constriction on both groups. The mean of time to deliver the nucleus was significantly longer in the group II (4.38±2.51 min) than in the group I (1.98±1.61 min). There was significant difference on UCVA (p= 0.00067) and corneal thickness (p=0.0044) only on the first post-operative day. However, there was no significant difference on further evaluations (p>0.05). There were also no significant difference on flaremeter and SIA during follow -up. Conclusion : Both phacofragmentation and phacoemulsification techniques were effective and safe for cataract surgery on senile white mature cataract. Phacofragmentation technique therefore could be an alternative small incision cataract surgery. (Med J Indones 2003; 12: 94-102) Keywords : phacofragmentation, phacoemulsification, senile white mature cataract